Hybrid Warfare in Ukraine and its Impact on Climate Politics - CHAD M. BRIGGS; MIRIAM MATEJOVA (Czech Journal of International Relations)
The Russian invasions of Ukraine in 2014 and 2022 represented not only attempts to erase Ukrainian sovereignty but were also linked to a larger campaign by the Kremlin to undermine trust in democratic institutions, scientific data, and the resilience of Western societies. This form of hybrid warfare has long taken a particular focus on energy systems, both in attempts to maintain Russian oil and gas exports, and to target energy infrastructure in invaded states like Ukraine. This article briefly traces the origins of the Russian government’s “assault on truth,” revealing how the information battlespace has affected global climate politics. The disruption of climate politics has long been a goal of the Kremlin and its allies. We argue that the ongoing energy crisis must be approached carefully, with particular attention to countering anti-science and anti-climate efforts.